IS MANDATORY SUSTAINABILITY REPORT STILL BENEFICIAL? - Rudyanto, Astrid (Jurnal Akuntansi dan Keuangan Indonesia, 2021)
The latest regulations in Indonesia (SEOJK No 16/SEOJK.04/2021) have required public companies to make a sustainability report every year in order to increase sustainable investment. Prior to this regulation, several public companies had made sustainability reports and received benefits of sustainability report. This makes issuers ask whether after being obligated, public companies still get the benefits that have been obtained from voluntary sustainability reports and under what conditions the mandatory sustainability reports are beneficial for public companies. This study answers the public companies' doubts by conducting a systematic literature review on research on mandatory and voluntary sustainability reports in Q1 and Q2 journals from 2008-2018. Before answering the issuers' doubts, this study explains the reasons why issuers make voluntary sustainability reports and the benefits derived from voluntary sustainability reports. After that, based on previous research, this study explains whether the benefits obtained from voluntary sustainability reports can still be obtained in mandatory sustainability reports. This study found that sustainability reports were made because of the desire to benefit from these reports initiated by company leaders coupled with institutional pressure. The benefits of voluntary sustainability reports are the positive perception of shareholders and increased concern for the company's sustainability. Mandatory sustainability reports can still provide some (though not all) of the same benefits as voluntary sustainability reports. In addition, the sustainability report must be able to cover the weaknesses of the voluntary sustainability report with the condition that there is strict legal coercion, strict supervision, and the addition of an obligation to audit sustainability information which is strengthened by market demands to make a sustainability report. Therefore, the Indonesian government must pay attention to these conditions for this regulation to be implemented properly.